Virtual team learning: The role of collaboration process and technology affordance in team decision making - Sean Cordes (Knowledge Management & E-Learning: An International Journal, 2016)
The study examines two dimensions that impact virtual team decision making. One is the influence of collaboration process structure: the sequences, patterns, and routines participants use to interact and solve problems. The other is technology affordance: the strengths and weaknesses of technologies in terms of the usefulness they offer to teams when performing tasks. Some teams used a structured collaboration process with monitoring, coordination, and backup functions during a decision-making discussion. Other teams had no discussion process instructions. In addition, some teams possessed stronger technology affordance including both chat and an editable document. Other teams used chat technology alone, which offered fewer collaboration possibilities. The collaboration process and technology affordance factors were tested in an experiment in which four-person online teams worked as a personnel hiring committee. Information about four job candidates was distributed to create a hidden profile in which some information was shared across all team members, while other information was visible only to specific members. Two hundred and eight students, comprising fifty-two teams completed the study. Teams using the structured collaboration process made more accurate and higher-quality decisions. In addition, scores were higher when technology affordance included both chat and editable document tools, but this influence was not significant.